AUTHORS’ STRATEGIES FOR JUSTIFYING RESEARCH METHODOLOGY IN RESEARCH ARTICLES PUBLISHED IN PRESTIGIOUS JOURNALS - Risnawati, Risnawati; Arsyad, Safnil; Wardhana, Dian Eka Chadra (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
The dependability and validity of research outcomes depend on the quality of the arguments presented in scientific articles' methods sections, which also affects reproducibility. Previous discourse analysis studies have paid little attention to evaluating the importance of methods sections. This research examines how authors in applied linguistics and English education rationalize their methodological selections, concentrating on three main facets: research design, sampling methods, and data analysis. The study analyzed 100 scholarly articles from respected international journals included in Scopus and distributed across four separate regions. Authors typically supported their research design and data analysis by citing methodological literature but used implicit justification when selecting sampling methods. Several articles did not provide clear explanations for their methodological choices, particularly regarding sampling methods. The results reveal a significant gap between the anticipated standards for transparent methodological reporting and the currently observed scholarly practices. Research design and data analysis received frequent justifications, but sampling methods remained poorly explained, thus compromising both transparency and replicability. Researchers need to provide stronger direct justifications for all methodological aspects, according to this study. Novice authors and postgraduate students must carefully adhere to journal guidelines and provide complete and detailed reporting within the methods section.